Aplikasi Packet Diffusion Model untuk Menganalisis Pengaruh Fenomena Micromixing terhadap Jalannya Reaksi Kimia Paralel di dalam Reaktor Tangki reraduk Kontinyu dengan Aliran Umpan Terpisah - Ali Altway; Sugeng Winardi; M Rachimoellah (Forum Teknik, 2004)
The effect of turbulent  mixing on  the  course  of two fast parallel competitive  chemical reactions  (netralization  of sodium  biborate  snd  iodide-iodate  oxidation-reduction  reactions) carried  out  in  continuous  stiwed  tank  reaktors  have been  studied  theoretically,  using  PacketDiffusion  Model,  and  experimentally  to  validate  the  theoretical predictions.System studied  consists  of flat bottom  cylindrical  tank  0.2 m in  diameter.  The height of liquid  in  the  tank  is  also  0.2 m. The  tank  was equipped  with Fan Turbine  with diameter equal  to I/3  tank  diameter. Sulphuric  acid solution  (0.5  Il,Q was fed into  the  tank through  2 mm-diameter pipe,  and  the  aquous  solution containing 0.0909  M NaH2Boj,  0.0909  M H:Bo:,  0.0116667  M KI, and  0.0023333  M KIO3wasfed  into  the  tank  through  I0  mm-diameter  pipe.  The rate  of acid solution  was  varied  0,045,  0.068,  and 0.09  liter/minute,  while the  rate  of  the  other solution  was varied  I,  1.5,  and  2 liter/minute  (the  rate  variation  coruespond  to  the  mean residence  time variation of 6, 4, and 3 minutes). The  impeller  rotation  speedwas  varied;  9,12,  and  I5  rps.  The iodine  concenftation  in  the  tank  influent  was  analyzed  using  spectrophotometer.The  simulation  works  conclude  that  the  selectivity  of iodine  decrease  with  increasing impeller  rototion  speed for the  mean  residence  time of 3 and 4 minutes,  while for the  mean residence  time of  6 minutes,  the iodine  selectivity increase  with  increasing  impeller  rotation speed. Increasing  the  mean residence  time from 3 to  4 minutes will decrease  the  iodine selectivity, while  increasing  the  mean residence  time further to  6 minutes  will  increase  the selectivity.  The theoretical  prediction  using  Packet  Difusion  Model agree fairly well  with  the experimental data.  The  experimental studies  also  showed  that  the feed position  in  the  region  of high  turbulent  intensity  (impeller  region)  give  lower iodine  selectivity compaired  to  the selectivity  in  the  region  of lower  turbulent  intensity.  The  Packet  Dffision  Model  cannot simulate  the  effect  offeed  position  on the  iodine  selectivity.Keywords:  Packet  Diffusion Model, Micromixing, and  Continuous  Stirred  Tank  Reactor